Managing Tuberculosis and Occupational Health in the Mining Sector in Southern Africa - Osewe, Patrick L. (World Bank, Washington, DC, 2018)
Given the magnitude and the complexity of factors associated with tuberculosis (TB) in the mining sector in southern Africa, no sector or actor is solely equipped to effectively tackle the issue. A cross-border response to TB involves a number of policy, programmatic, and service delivery considerations and the success of these efforts largely depends on establishing effective coordination and implementation mechanisms that bridge the mines, communities, and countries including the housing, labor, health and mining sectors; development partners; civil society; labor unions; and mineworkers. Through its South Africa Health Knowledge Hub (the Knowledge Hub), established in 2012, the World Bank Group (WBG) has worked extensively in the southern Africa region to support sustainable health reform and promote investments in all sectors that form the foundation of healthy societies. The WBG’s Health, Nutrition and Population (HNP) Global Practice has served as a vital source of financial and technical assistance in South Africa, facilitating high-level dialogue, multispectral and public-private engagement, knowledge generation, and implementation support to tackle long-standing health sector challenges, including the persistent challenge of TB in the mining sector. This compendium assembles a rich and diverse collection of papers, reports, and other material generated through technical assistance to tackle TB in the mining sector in southern Africa, spearheaded by the World Bank’s Southern Africa Knowledge Hub. The historical context details the significant progress and achievements made since the Hub was formally established in 2012. Particularly important is the documentation of work done on harmonization often a challenge when working across sectors to develop a multisectoral approach. The information provides readers with the understanding necessary to examine the policy and practitioner approaches that have been used thus far and captures the successes, challenges, collaborations, and lessons learned in carrying out a range of comprehensive studies and innovative interventions.